An explorative study into the use of restrictive practices in an adult forensic mental health inpatient setting - Barr, Lesley Anne (Curtin University, 2022)
Reducing or eliminating restrictive practices (specifically seclusion, restraint, and Pro Re Nata [PRN] psychotropic medications), is a global health priority due to the risk of patient harm, workforce stress, injury, and human rights issues. The aim of this research was to explore the use of restrictive practices in the acute forensic mental health inpatient setting (AFMHIS). A multiphase mixed method research design (QUAN-qual) was used, with three quantitative and one qualitative research studies conducted in an AFMHIS in Australia. The use of a mixed methods research design facilitated a comprehensive exploration of a complex phenomenon from multiple perspectives and offered unique insights which can inform practice and policy development.